Effect of DIN and DON sources on the nitrogen uptake of the seagrass Zostera japonica and the macroalgae Ulva pertusa previously grown in different light levels - Han, Qiuying; Qiu, Chongyu; Zeng, Wenxuan; Chen, Yu; Zhao, Muqiu; Shi, Yunfeng; Zheng, Fengying (Frontiers in Marine Science, 2023)
This study quantified the absorption ability of the seagrass Zostera japonica and the macroalgae Ulva pertusa for dissolved inorganic nitrogen (DIN) (ammonium and nitrate) and dissolved organic nitrogen (DON) (urea and glycine) under different light conditions. The plants were cultured in filtered seawater (31‰, 25°C) for 2 weeks under three light levels. Macroalgae and the above- and belowground parts of seagrasses were separately placed into four different manmade seawater solutions with DIN (ammonium and nitrate) and DON (urea and glycine) stable isotopes for 1 h. The results showed that macroalgae had higher absorption rates for ammonium and nitrate after higher light (14.67 ± 2.50 and 1.29 ± 0.16 mg−1 dry weight (DW) h−1) than after lower light (4.52 ± 0.95 and 0.18 ± 0.12 mg−1 DW h−1) treatments. Compared to the belowground seagrass portions that had previously been grown in high and low light conditions, the seagrass leaves assimilated ammonium more quickly. Z. japonica preferred glycine to nitrate and urea after the high- and low-light treatments; that is, the absorption rates of the belowground seagrass parts for glycine were 14.71 ± 1.85 and 6.38 ± 0.52 mg−1 DW h−1 after the high- and low-light treatments, respectively, which were higher than those of ammonium, nitrate, and urea. The absorption rates of algae were lower than those for ammonium previously grown under medium- and low-light treatments. These results indicate that light reduction can impact the assimilation of DIN by Z. japonica and U. pertusa, and both have the ability to directly assimilate DON. This study provides information that could help reduce the negative effects of eutrophication on macroalgae and seagrasses in order to protect seagrass meadows.